Phosphate recovery from sewage sludge supernatants using magnetic nanoparticles - SEMERCİ, NESLİHAN; GENÇ, SEVAL; CAN, ZEHRA SEMRA (ELSEVIER, 2021)
Phosphorus removal and recovery from synthetic solutions and sewage sludge supernatants by using magnetic nanoparticles (MNP) were investigated through batch adsorption experiments. The adsorption kinetics and isotherms on the removal of phosphate have been studied using different MNP doses, contact time, pH, and initial P concentrations. Reusability of the MNP and the enrichment of phosphate in desorption solution from dewatering supernatants were tested in a series of adsorption-desorption cycles. The removal efficiency was between 29 and 97 % after 24 h depending on the P concentrations and adsorbent concentrations. This efficiency was detectable in pH similar to 3-5 but decreased in case of increased pH levels. Intra particle (IP) diffusion model kinetic tests demonstrated that the adsorption process was controlled by a multi-step mechanism and the reaction equilibrium was reached after 120 min. Besides phosphate, ammonium, magnesium and calcium ions were adsorbed on MNP to a lesser extent. Surface characterization and adsorption mechanism were discussed based on XRD, SEM and FTIR analyses. MNP can be very effective for both ammonia and phosphate removal and recovery from dewatering supernatant solutions.
Keywords: Magnetite; Phosphate removal; Phosphate recovery; Adsorption; Desorption